Cell wall degradation of Chlorella vulgaris under darkness and ultraviolet irradiation-B (UVB) conditions for lipid and carbohydrate recovery - Md Nadzir, Syafiqah; Yusof, Norjan; Nordin, Norazela; Kamari, Azlan; Mohd Yusoff, Mohd Zulkhairi (UPM, 2022)
The production of microalgae biofuel is still not economically viable due to the high cost of downstream processing, which is attributed to cell harvesting and disruption processes. In this study, the biochemical and structural changes of Chlorella vulgaris UPSI JRM01 that was cultivated under darkness for 13 days and ultraviolet irradiation-B (UVB) (0, 15, 30, 60, 120, and 180 min) stress conditions to induce cell wall degradation were investigated. Under the condition of darkness, C. vulgaris invested their fixed carbon towards the accumulation of carbohydrates (35 %) instead of lipids (25 %). Meanwhile, the highest lipid and carbohydrate content obtained under UVB were 34.4 % and 47.5 %, respectively. The cell wall thickness of culture stained with calcofluor white (CFW) observed under fluorescence microscopy revealed that degradation of cell wall occurred under darkness on the seventh day (0.076 ± 0.037 μm) and 30 min of UVB irradiation (0.091 ± 0.044 μm). The transmission electron microscopy (TEM) micrographs further confirm the cell wall thinning under both conditions. Cell wall polysaccharides content measured under darkness and UVB conditions were 4.3 % and 6.6 %, as compared to control 11.3 % and 10.2 %, respectively. These results show that darkness and UVB stress are feasible means to induce cell wall degradation for lipid and carbohydrate recovery.